(untitled) (SAARC Journal of Agriculture, 2019)
The effects of two tillage methods (zero tillage and conventional tillage), two residue managements (residue kept and residue removed) and two levels of cropping system (maize + soybean and sole maize) were studied over 3 years (2015-2017) at Dailekh district of Nepal. Arun-2 and Puja were the varieties of maize and soybean used respectively, followed by winter wheat. The results revealed that the maize + soybean system had significantly higher plant population and ear population (34.83 thousands ha-1 and 34.35 thousands ha-1, respectively), grains per row (37.1), ear length (16.6 cm) and 20.5% higher grain yield as compared to sole maize. The highest maize equivalent yield (7.92 t ha-1) was recorded in maize + soybean as compared to the lower grain yield equivalent (7.06 t ha-1) in sole maize. Zero tillage accounted relatively higher benefits (high net income and B:C ratio) as compared to conventional tillage. The residue kept plot resulted significantly higher B:C ratio (2.41) than the residue removed (2.11) and the maize + soybean recorded 82.5% greater B:C ratio compared to sole maize. Net annual income was significantly higher in zero tillage, residue kept and maize + soybean system (NRs. 223072.00, 222958.00 and 269016.00 ha-1 respectively). Such combinations are recommended for Dailekh district of Nepal to have profitable crop productivity. SAARC J. Agri., 17(1): 49-63 (2019)